Indonesian University Students’ Common Mistakes when Formulating Interrogative Sentences with ‘Wh-questions’ - Rentauli Mariah Silalahi (Soegijapranata Catholic University, 2017)
This study investigated the most common mistakes university students made when formulating interrogative sentences using the ‘Wh-questions: Who, What, Whom, Which, Whose.’ The research was initiated by the researcher’s curiosity when finding out that students in IIE university (pseudonym) frequently made mistakes when trying to ask questions using the ‘Wh-question’ in almost every occasion; either in classrooms or in general lectures. The research which was conducted using descriptive qualitative method involving 60 university students as direct participants, who received some treatments found out that students’ most common mistakes were about choosing the right ‘Wh-question’ to form the question and to place every component that built the question in a correct order and the other mistakes were related to the right use of article, demonstrative, verb, an auxiliary verb, while little problem was related to a problem with diction and ability to make meaningful sentence. The study also found out that the IIE students made more mistakes than ever anticipated by Swan (1980) and that there was a close inseparable connection among all grammatical issues when composing any sentence in English.